EVALUASI SISTEM PENGENDALIAN INTERNAL SISTEM PENJUALAN KREDIT PADA PT ARINGO COMPUTER - Makmur Makmur; Muhammad Kadafi; Apria Apria (Politeknik Negeri Samarinda, 2019)
In order to achieve the company's purpose is to get maximum profit, the company needs a tool used in order to achieve the company. The tools are accounting system and reports of each section used to provide financial information for the company. The purpose is to know the appropriateness of applying credit sales system based on internal control system principle. In the data collection, the authors conducted several interviews, observation, interviews and study the source of the book (literatures). The analytical tool used is the elements of internal control system of credit sales by Mulyadi and the main purpose of internal control system. The result of this research is there are some system applied by company which is not in accordance with Internal Control System so that can cause loss for company. Keywords: Accounting System, Credit Sales System, Internal Control System.